Composite Rice Flour Products for Noodle Industry : Kanom – jeen - Onanong Naivikul; Chittana Chammek; Sineenart Chariyachotilert; Lalana Youngprasittiporn (Agriculture and Natural Resources, 1990)
Pregelatinized rice flour was mixed with rice flour and rice starch to produce Kanom – jeen in order to shorten the time of preparation. It was found that pregelatinized rice flour could be prepared by mixing with 40% by weigh of water and slurry fed to the drum drier with the spacing set at 0.004 inch, the drum rotation was set at 28 rpm. and the steam pressure at 40 psi. The sheet was ground and passed through a 1 mm. sieve. The resulting flour was a white glossy powder which had a moisture content of 5.2%. The flour had a hydration capacity of 11.5 times and had a viscosity of 85 Brabender Units at 30oC, while normal flour still showed a reading of zero at this temperature. A comparison of Kanom-jeen, made from pregelatinized rice flour in a ratio of 15:85, and the second from pregelatinized rice flour, rice starch and rice flour in a ratio of 15:30:55, showed that there were no significant difference in yield, maximum cutting stress and preference test, but there was a significant difference in resistance to compression during the production.